Stressless selling : a guide to success for men & women in sales - Stern, Frances Meritt (London, United Kingdom : Prentice-Hall, 1981)
It's a fact that all of us experience stress. It can be constructive stress, such as the positive, mobilizing, energizing stress a speaker experiences before speaking or an athlete before competing. Or it can be negative, immobilizing stress - an unexpected, nasty retort from a prospect or a sudden skid on a patch of ice - that can cause us to panic and momentarily "freeze up." Sometimes the stress we encounter leads us to experience strain or tension that is short-lived and mild. And that's fine, because it adds excitement and pleasure to what we do. Some event (or series of events), the anticipation of an event, even the mental re-living of a past event seem to trigger a temporary anxious or nervous reaction - a sort of tension or disquiet. At other times, we experience severe, debilitating stress that seems to build slowly and go on forever. It can disrupt our ability to concentrate, create, problem solve, eat, sleep, laugh, love, and generally enjoy life in its most whole, robust, and rewarding forms. And it happens to the best of us.
Section One. Sorting Out The Stress Mess: What's Fact, What's Fiction -- Section Two. Developing Your Personal Stress Profile and Your Personal Stress-Management Prescription -- Section Three. Stress-Management Strategies that work.
Includes bibliographical references.
Keywords: SALES PERSONNEL